The Artistic and Dramatic Values of the Okposo Festival of the Itsekiri People of Ugbuwangue - Ovie-Jack, Matilda Eyituoyo (NIU Journal of Social Sciences, 2020)
The Okposo festival of the Itsekiri people of Ugbuwangue is highly spiritual. It recreates in dramatic and poetic mode the people's closeness to the marine (Okun) ecology of the Niger Delta. Its yearly enactment has served in recent years as not only a means of cultural unification but also a platform family renewal. The festival has as part of its aesthetic realization, the complete elements of modern theatre such as dance, song, ritual, costume, chants, and imitation. This paper thus examines the cultural values and dramatic aesthetics that constitute the performance of the Okposo festival of the Itsekiri people of Ugbuwangue in a bid to highlight the elements of drama and its modes of cultural redefinition in contemporary societies. The paper adopts the participant observation method as the theoretical framework to enable us obtain adequate information from the society and interpret same with regards to the metaphor of traditional theatre and ritual efficacy of African festivals. The paper concludes that African festival not only serves as a means of entertainment but also as a mode of preserving the cherished cultural values of the people. Keywords: Aesthetics, Festival, Itsekiri, Okposo.